PEMANFAATAN SERBUK GERGAJI KAYU UNTUK BUDIDAYA JAMUR TIRAM PUTIH (PLEUROTUS OSTREATUS) DI KELOMPOK MASYARAKAT DESA PASIR KIDUL - Eti Wahyuningsih; Indah Sulistiyawati; Nur Laila Rahayu (Pusat Pengabdian kepada Masyarakat- LPPM Universitas Terbuka, 2022)
Pasir Kidul Village is one of the industrial villages in West Purwokerto District, Banyumas. Wood industrial waste (pencil factory), namely wood sawdust and wood chips accumulate and disturb the surrounding environment. One of the uses of this waste is the raw material for white mushroom baglog (Pleurotus ostreatus). This Community Partnership Program (PKM) aims to utilize wood sawdust for the cultivation of white oyster mushroom (Pleurotus ostreatus) in community groups in Pasir Kidul Village, West Purwokerto District, Banyumas Regency. This PKM is held for 5 months, from August to December 2018. There are 19 community groups in this community partnership program, with the target that after counseling, training and assistance in the application of